Tailoring Material Properties of Duplex Stainless Steel by DED-LB/M and In-situ Alloying with Elemental Powders - Maier, Andreas; Rühr, Manuel; Stephan, Marcel; Frankl, Sebastian; Roth, Stephan; Schmidt, Michael (Journal of Laser Applications, 2023)
Stainless steels are established in various fields with challenging environments, e.g. offshore, petrochemical, and automotive industries. The combination of high-performance properties and high-value added applications makes stainless steels attractive for Additive Manufacturing (AM). In powder-based AM processes such as Laser Directed Energy Deposition (DED-LB/M) typically pre-alloyed powders are used for part generation. By an innovative approach called in-situ alloying, the chemical composition of pre-alloyed powder can be adjusted by mixing it with an additional powder material. This allows the material properties to be flexibly and efficiently tailored for specific applications. In this work, a standard duplex stainless steel (DSS) is modified for the first time with elemental powders in order to systematically adjust the resulting phase formation, mechanical properties and corrosion resistance. For this, powder mixtures were generated consisting of pre-alloyed DSS 1.4462 and additions of pure Chromium (1.0 to 7.0 wt.%) or Nickel (1.0 to 5.0 wt.%) powder. Processing them by means of DED-LB/M resulted in specimens (rel. density > 99.7 %) with ferrite-austenite phase ratios ranging from almost 10:90 % to 90:10 %. Increasing the Chromium content successively increased the ferrite percentage, resulting in higher material hardness, higher strength and resistance against pitting corrosion, but poor ductility and toughness compared to unmodified DSS. In contrast, an increased Nickel content resulted in an increased austenite formation with lower hardness and strength, but increased ductility. This strategy was shown to add flexibility to powder-based AM processes by enabling an on-demand material design for stainless steel
Keywords: Additive Manufacturing; Directed Energy Deposition; In-situ Alloying; Stainless Steels; Microstructure; Mechanical Properties; Corrosion Resistance